Trapping of ultra-cold atoms with the magnetic field of vortices in a thin-film superconducting micro-structure - Müller, T. (2014)
We store and control ultra-cold atoms in a new type of trap using the magnetic fields of vortices in a high-temperature superconducting micro-structure. We generate the attractive trapping potential for the atoms by combining the magnetic field of a superconductor in the remanent state with external homogeneous magnetic fields. We show the control of crucial atom trap characteristics such as an efficient intrinsic loading mechanism, spatial positioning of the trapped atoms and the vortex density in the superconductor. The measured trap characteristics are in good agreement with our numerical simulations.